Bank Runs and Institutions: The Perils of Intervention - Ennis, Huberto M; Keister, Todd (American Economic Review, 2009)
We study ex post efficient policy responses to a run on the banking system and the ex ante incentives these responses create. We show that the efficient response to a run is typically not to freeze all remaining deposits, since doing so imposes heavy costs on some individuals. Instead, once a run is underway, (benevolent) government institutions would allow additional deposit withdrawals, placing further strain on the banking system. When depositors anticipate these extra withdrawals, their incentive to participate in the run increases. In fact, ex post efficient interventions can generate the conditions necessary for a self-fulfilling run to occur. (JEL G21, G8)